Bridging The Gap Between Policy And Practice: A Structural Equation Modeling Of Kurikulum Merdeka Implementation And School Quality Improvement In Indonesia - Rokimin; Imam Khairul Annas; Muhammad Fatih Azka; Nurkholis Nuri; Nesa Novrizal (At-Tathbīq: Journal of Education and Learning, 2026)
Purpose of the Study: This study aims to analyze the relationships among the determinants of Kurikulum Merdeka implementation and their influence on school quality improvement through a conceptual Structural Equation Modeling (SEM) framework derived from a Systematic Literature Review (SLR). The study examines the roles of teacher readiness, principal leadership, and school support in promoting effective curriculum implementation and enhancing school quality. Methodology: This research employs a Systematic Literature Review using the PRISMA protocol. Data were collected from Scopus- and Sinta-indexed scholarly articles published between 2020 and 2026 on the implementation of the Kurikulum Merdeka, teacher readiness, principal leadership, school support, differentiated learning, and school quality. From an initial pool of 280 articles, 45 eligible studies were selected and synthesized to develop a conceptual SEM framework illustrating the relationships among the variables. Main Findings: Teacher readiness, principal leadership, and school support are the most influential determinants of successful Kurikulum Merdeka implementation. Furthermore, curriculum implementation functions as a significant mediating variable linking these determinants to school quality improvement. Effective implementation contributes to enhanced instructional quality, improved student learning outcomes, and stronger overall school performance. Novelty/Originality of this Study: This study presents a comprehensive conceptual SEM framework that integrates teacher readiness, principal leadership, school support, Kurikulum Merdeka implementation, and school quality improvement into a unified model. It highlights the mediating role of curriculum implementation in transforming organizational and human resource capacities into measurable school quality outcomes, while synthesizing evidence from recent literature to support future empirical SEM research in Indonesian education.